Notes on three closely related species of the genus Pimoa (Araneae, Pimoidae) from Southwest China - Bing Wang; Qingzhen Meng; Zhiyuan Yao; Xiaoqing Zhang (Zoosystematics and Evolution)
The genus Pimoa Chamberlin & Ivie, 1943, is highly diverse and currently contains 85 species, of which 67 are distributed in Asia. In this study, a new species of Pimoa is described from Southwest China: P. shimian Wang, Yao & Zhang, sp. nov. (♂♀). This new species is closely related to P. bomi Zhang & Li, 2021, and P. reniformis Xu & Li, 2007. The taxonomic keys for distinguishing these three closely related species and a distribution map of all Asian pimoids are also provided.